2000
DOI: 10.1074/jbc.275.2.817
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of Laminin Induced by Acidic pH

Abstract: The supramolecular architecture of the basement membrane is provided by two enmeshed networks of collagen IV and laminin. The laminin network is maintained exclusively by interactions among individual laminin molecules and does not depend on the presence of other extracellular matrix components. Laminin polymers can be obtained in vitro either in solution or in association with the surface of bilayers containing acidic lipids. In this work, we have tested the hypothesis that the negative charges present on aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 41 publications
1
50
0
1
Order By: Relevance
“…Assembly of laminin-111 triggered by a local acidic pH at the cell surface 38 has been suggested as a mechanism to explain observations that in vivo protein levels in BMs may be lower than gelation thresholds observed in vitro. 24 Our results potentially agree with this mechanism, as the resultant gels have structure similar to BMs in vivo. 39 It is also possible that decreasing pH interferes with the solubility of the protein in urea.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Assembly of laminin-111 triggered by a local acidic pH at the cell surface 38 has been suggested as a mechanism to explain observations that in vivo protein levels in BMs may be lower than gelation thresholds observed in vitro. 24 Our results potentially agree with this mechanism, as the resultant gels have structure similar to BMs in vivo. 39 It is also possible that decreasing pH interferes with the solubility of the protein in urea.…”
Section: Discussionsupporting
confidence: 80%
“…Although the ECM mechanism of assembly in vivo is not clear, it has been suggested that BM assembly in vivo is induced by a reduction in pH at cell surfaces. 24,25 These extracts may provide a tool for studying this process. All tissue extracts could be assembled into gels by acid mechanisms of gelation and maintained this structure at pH 7.4 and 378C.…”
Section: Gelationmentioning
confidence: 99%
“…First, our previous work had suggested that negative lipids could modulate laminin self-assembly (Freire and Coelho-Sampaio, 2000;Freire et al, 2002). Second, we knew that surface charges had been proposed to fine-tune the cellular response to ECM molecules, such as chondroitin and heparan sulfate proteoglycans (Powell et al, 1997;Wettreich et al, 1999).…”
Section: Figmentioning
confidence: 99%
“…More recently, we showed that solution polymerization could alternatively be triggered at low laminin concentrations by acidification of bulk pH (Freire and Coelho-Sampaio, 2000). We hypothesized that acidic polymerization may occur in vivo in regions of the plasma membrane where circumstantially the negatively charged groups provided by glycoproteins, glycolipids and proteoglycans reduce the local pH (Wettreich et al, 1999;Freire and Coelho-Sampaio, 2000).…”
Section: Introductionmentioning
confidence: 99%